Expanding of atrophic mandibular alveolar ridge using bone splitting technique simultaneously dental implantation with bovine bone graft ( clinically and radiologically study ) (Journal of Hama University, 2020)
this study aimed to evaluate the Bone gain after using bone splitting technique simultaneously dental implantation with bovine bone graft. For this study, 15 cases of  atrophic mandibular alveolar ridge by using bone splitting technique simultaneously dental implantation with bovine bone graft installed in 8 patients (average patients age range between 25 and 62 years ) . gained width measured by cbct (cone beam computed tomography) before the surgical operation and  immediately after the surgical operation and measured bone resorption  after observation  of six months.The medium of The Bone gained width immediately after the surgical operation was (3.41± 1.09) mm and The medium of The Bone resorption after six months of implantation from buccal wall of implant (2.22 ±1.52) mm and from lingual wall (0.41 ± 0.64) mm.Results of this study, bone splitting technique simultaneously dental implantation with bovine bone graft consider effective method in increase width of alveolar ridge with minimal bone resorption on buccal bone   With success rate 100% ,  reduce the need of more surgeries and reduce treatment time .